SISTEM INFORMASI GEOGRAFIS (SIG) PEMETAAN LOKASI PENJAHIT PAKAIAN DI KOTA TEMBILAHAN BERBASIS WEB - Nurita Suwanti; Usman Usman (Indragiri Islamic University, 2021)
Currently, there are many information systems that are used to support and solve a problem that usually arises in an organization, company or government agency. One of them is Geographic Information System (GIS) technology which has developed rapidly. Where this system can be a means for delivering information on the location of the location, especially those related to the business of tailoring clothes. This geographic information system for mapping the location of the tailor's location aims to analyze, design and build a geographic information system for mapping the location that can convey information on the location of the tailor, convey complete information about the tailor's location so that it can be spread thoroughly to the public or system users, provide useful information to the public in the process of finding the location of tailors in Tembilahan city based on precise and accurate data. In designing the GIS mapping of the tailor's location, Waterfall is a system development method that functions as a mechanism to identify software, as well as UML (Unified Modeling Language) as modeling, and uses the PIECES method to facilitate researchers in building systems. With the geographical information system mapping the location of this tailor, the delivery of information about the tailor's place can be spread thoroughly to the community or system users. Keywords: System, Information, Geographic Information System, Tailor,WebGis.